PERFORMANCE ASSESSMENT OF NON-PROFIT ORGANISATIONS IN MODERN CONDITIONS - Rogach, Olga; Frolova, Elena; Demina, Svetlana; Morozova, Lyubov; Danilova, Veronika (Revista Inclusiones, 2020)
The article presents the materials of a survey of Moscow residents in order to assess the activities of non-profit organizations in modern conditions. The leading method of the study was a telephone survey of respondents based on random generation of telephone numbers. The sample selection consisted of 1006 respondents aged over 18 years. The gender and age of the residents of the Moscow city became the signs of representativeness. The authors define the factors that determine the public’s attitude to the third sector: age, level of education, degree of involvement in the work of NPOs, the experience of actual practices of interaction, the level of awareness of NPO activities. The expectations of Moscow residents in relation to NPOs are connected with the need to solve acute social problems, to provide charitable assistance to socially vulnerable groups of the population. Narrowly professional activities of NPOs such as independent public control, human rights activities are perceived as secondary. Despite the fact that more than half of respondents positively assess the activity of NPOs (55%), there are negative trends in the attitude of Moscow residents to the third sector: a low level of trust, stereotypical perception of its functions. In some cases, the assessment of the activities of non-profit organizations is based on superficial knowledge, which is due to the lack of most of the respondents of real interaction with NPOs, and of low level of awareness about their activities. K